3D Structure, Dimerization Modeling, and Lead Discovery by Ligand‐protein Interaction Analysis of p60 Transcription Regulator Protein (p60TRP). Issue 3 (20th July 2015) - Pramanik, Subrata; Kutzner, Arne; Heese, Klaus
Abstract: The p60 transcription regulator protein (p60TRP) is a basic helix‐loop‐helix (bHLH) domain‐containing neuroprotective protein and a member of the G‐protein‐coupled receptor (GPCR)‐associated sorting protein (GPRASP) family. In the present study, multiple theoretical physico‐chemical methods (e.g. Modeller v.9.13, I‐TASSER, PROCHECK and ClusPro v2.0 with PIPER) were applied to unveil the three‐dimensional (3D) protein structure of the p60TRP homo‐dimer protein and explore potential ligand‐protein interactions. Our results suggest a Mg 2+ ‐containing 3D p60TRP dimer protein that potentially interacts with 5‐(1‐aziridinyl)‐2, 4‐dinitrobenzamide (CB1954) and [2‐(3‐dodecylimidazolidin‐1‐yl)‐1‐phosphonoethyl] phosphonic acid (B73). The discovery of CB1954 and B73 may serve as a potential lead for further drug screening tests to normalize the p60TRP signaling pathway in neurodegenerative diseases. Interference with p60TRP signaling via CB1954/B73‐related molecules might be a novel option for modifying neurodegenerative signaling pathways (e.g. RIN1, PP2A, RanBP5, CREB and SYNJ1) to treat various brain diseases. Abstract :